The Price per Prospective Consumer of Providing Therapist Training and Consultation in Seven Evidence-Based Treatments within a Large Public Behavioral Health System: An Example Cost-Analysis Metric - Kelsie H. Okamura; Kelsie H. Okamura; Courtney L. Benjamin Wolk; Christina D. Kang-Yi; Rebecca Stewart; Ronnie M. Rubin; Shawna Weaver; Arthur C. Evans; Zuleyha Cidav; Rinad S. Beidas; David S. Mandell (Frontiers in Public Health, 2018)
ObjectivePublic-sector behavioral health systems seeking to implement evidence-based treatments (EBTs) may face challenges selecting EBTs given their limited resources. This study describes and illustrates one method to calculate cost related to training and consultation to assist system-level decisions about which EBTs to select.MethodsTraining, consultation, and indirect labor costs were calculated for seven commonly implemented EBTs. Using extant literature, we then estimated the diagnoses and populations for which each EBT was indicated. Diagnostic and demographic information from Medicaid claims data were obtained from a large behavioral health payer organization and used to estimate the number of covered people with whom the EBT could be used and to calculate implementation-associated costs per consumer.ResultsFindings suggest substantial cost to therapists and service systems related to EBT training and consultation. Training and consultation costs varied by EBT, from Dialectical Behavior Therapy at $238.07 to Cognitive Behavioral Therapy at $0.18 per potential consumer served. Total cost did not correspond with the number of prospective consumers served by an EBT.ConclusionA cost-metric that accounts for the prospective recipients of a given EBT within a given population may provide insight into how systems should prioritize training efforts. Future policy should consider the financial burden of EBT implementation in relation to the context of the population being served and begin a dialog in creating incentives for EBT use.